Investigating the Effectiveness of Peer Feedback in Developing Critical Thinking Skills in Undergraduate Students - Phoolan Chakarvarti (Journal of Education Review Provision, 2022)
The purpose of this research was to determine whether or not undergraduates benefitted from receiving input from their peers when it came to the development of their critical thinking skills. A total of 60 freshmen taking an introductory philosophy course at a major public university in the United States served as the study's sample for a pre-test, post-test control group design. Students in the experimental group had their critical thinking tasks reviewed by their peers, while those in the control group did not. Changes in critical thinking were measured using the California Critical Thinking Skills Test (CCTST). The results of the CCTST showed that the experimental group had significantly higher levels of critical thinking than the control group. This result demonstrates the potential of peer feedback as an instructional strategy for fostering critical thinking in undergraduates. Student access to chances for group study is also highlighted. These results have substantial repercussions for classroom practice. Peer feedback is a useful tool for teachers to help their pupils develop the critical thinking skills necessary for success in school and the workplace. Important social and cognitive skills, such as communication, collaboration, and critical thinking, can be fostered in students through collaborative learning tasks.